Examining dietary self-talk content and context for discretionary snacking behaviour: a qualitative interview study. Issue 1 (31st December 2022) - Rose, Jordan; Pedrazzi, Rebecca; Dombrowski, Stephan U.
ABSTRACT: Background: Consuming discretionary snack foods high in calories, salt, sugar or fat in between regular meals can have a negative impact on weight management and health. Despite the intention to refrain from discretionary snacking, individuals often report feeling tempted by snack foods. A cognitive process to resolve food choice related tension may be dietary self-talk which is one's inner speech around dietary choice. This study aimed to understand the content and context of dietary self-talk before consuming discretionary snack foods. Methods: Qualitative semi-structured interviews based on Think-Aloud methods were conducted remotely. Participants answered open-ended questions and were presented with a list of 37 dietary self-talk items. Interview transcripts were analyzed thematically. Results: Interviews ( n  = 18, age: 19–54 years, 9 men, 9 women) confirmed the frequent use of dietary self-talk with all 37 content items endorsed. Reported use was highest for the self-talk items: 'It is a special occasion'; 'I did physical activity/exercise today'; and 'I am hungry'. Three new items were developed, eight items were refined. Identified key contextual themes were: 'reward', 'social', 'convenience', 'automaticity', and 'hunger'. Conclusions: This study lists 40 reasons people use to allow themselves to consume discretionary snack foods and identifies contextual factors of dietary-self talk. All participants reported using dietary self-talk, with variation in content, frequency and degree of automaticity. Recognising and changing dietary self-talk may be a promising intervention target for changing discretionary snacking behaviour.